1992
DOI: 10.2337/diacare.15.11.1800
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Experience with an Exercise-Based Outpatient Life-Style Modification Program in the Treatment of Diabetes Mellitus

Abstract: Exercise is frequently recommended in the treatment of diabetes mellitus. Nevertheless, its use has been limited in clinical practice, and concerns about safety and efficacy persist. We have reviewed a 10-yr experience with 255 patients enrolled in a comprehensive diabetes program that emphasized physical training. A low maximal oxygen uptake (VO2max) was found in patients with non-insulin-dependent diabetes mellitus compared with sedentary control subjects. This was not accounted for by autonomic neuropathy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(70 citation statements)
references
References 22 publications
5
61
0
4
Order By: Relevance
“…Our results are comparable with those observed by others in adults with IDDM (McCargar et al, 1991;Wallberg-Henriksson et al, 1986;Yki-Ja Èrvinen et al, 1984;Wallberg-Henriksson et al, 1982;Schneider et al, 1992;Zinman et al, 1984;WallbergHenriksson et al, 1984). Failure to show any changes in resting heart rate may be explained by the fact that the measurement was not made after a suf®cient period of rest and because participants did not achieve the required exercise intensity (Ekelund et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are comparable with those observed by others in adults with IDDM (McCargar et al, 1991;Wallberg-Henriksson et al, 1986;Yki-Ja Èrvinen et al, 1984;Wallberg-Henriksson et al, 1982;Schneider et al, 1992;Zinman et al, 1984;WallbergHenriksson et al, 1984). Failure to show any changes in resting heart rate may be explained by the fact that the measurement was not made after a suf®cient period of rest and because participants did not achieve the required exercise intensity (Ekelund et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…Most metabolic studies find a significant effect of exercise on glucose control [22][23][24] and on triglycerides. 25,26 A meta-analysis of clinical trials on the effect of exercise on glucose control found that interventions longer than 8 weeks reduced HbA1c from 8.31% to 7.65% (weighted mean difference 0.66%, PϽ0.001) independently of body mass.…”
Section: Discussionmentioning
confidence: 99%
“…However, compliance to lifestyle changes has been proven to be poor in the long term [10]. In the last decades, bariatric surgery has emerged as a potential therapy for diabetes [11].…”
Section: Introductionmentioning
confidence: 99%